Answer:
-6s-c+1
Step-by-step explanation:
(-3s-4c+1)+(-3s+3c)
We have been given the above expression. To find the sum, we simply collect the like terms and combine them;
(-3s-4c+1)+(-3s+3c) = -3s + -3s -4c + 3c + 1
-3s + -3s -4c + 3c + 1 = -3s - 3s + 3c - 4c + 1
-3s - 3s + 3c - 4c + 1 = -6s - c + 1
Therefore;
(-3s-4c+1)+(-3s+3c) = -6s-c+1
Match each label to the correct location.
Answer:
x = 2
Step-by-step explanation:
Similar triangles are triangles which have the same shape but not the same size. This means their angle measures are equal but their side lengths are not instead they are proportional. To solve, we will set up a proportion and solve.
A proportion is two equal ratios set equal to each other. We form the ratios by finding corresponding sides (sides which match to each other on both triangles by their position). Out ratios will be one side of the small triangle over the corresponding side on the big triangle as shown below:
.
To solve the proportion, we'll cross multiply by multiplying numerator with denominator across the equal sign.
We have y - 2 = m(x + 5), where m = (-1 - 2)/(10 + 5) = -3/15 = -1/5;
Then y - 2 = (-1/5)(x + 5);
5y - 10 = (-1)(x + 5);
5y - 10 = -x - 5;
x + 5y - 5 = 0 is the equation of the line.
Answer:
b. 160°
Step-by-step explanation:
angle A = (far arc - near arc)/2
far arc is arc BC and near arc is arc BE. Replacing into the equation:
∠A = (arc BC - arc BE)/2
50 = [4x + 20 - (2x - 10)]/2
50*2 = 2x + 30
x = (100 - 30)/2
x = 35°
Replacing this information into arc BC equation:
arc BC = 4(35) + 20 = 160°